2014
DOI: 10.1155/2014/360230
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Flanking Secondary Structures on Amino Acid Content and Typical Lengths of 3/10 Helices

Abstract: We used 3D structures of a highly redundant set of bacterial proteins encoded by genes of high, average, and low GC-content. Four types of connecting bridges—regions situated between any of two major elements of secondary structure (alpha helices and beta strands)—containing a pure random coil were compared with connecting bridges containing 3/10 helices. We included discovered trends in the original “VVTAK Connecting Bridges” algorithm, which is able to predict more probable conformation for a given connectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…For the prediction of secondary structure elements, we used our original propensity scales . Those scales are based on the data obtained from the analysis of three‐dimensional structures of proteins with the maximal similarity of their amino acid sequences equal to 25% . So, we can state that the method we used is a kind of purely ab‐initio method and not homology‐based one.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the prediction of secondary structure elements, we used our original propensity scales . Those scales are based on the data obtained from the analysis of three‐dimensional structures of proteins with the maximal similarity of their amino acid sequences equal to 25% . So, we can state that the method we used is a kind of purely ab‐initio method and not homology‐based one.…”
Section: Resultsmentioning
confidence: 99%
“…To build that scale, we analyzed the amino acid content of alpha helices, beta strands, and random coil regions of 542 proteins from bacteria with different average genomic GC‐content. We used the same set of proteins that has already been described in our work on the 3/10 helices properties . There was no bias in that set associated with the design of the previous study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A specific analysis of a 3 10 -helix adjoining the α-helix and β-strand has shown that the composition of 3 10 -helices and β-strands is much more conserved among family members of homologous structures than those adjacent to two helices [26]. The preferred length of the 3 10 -helix occurring between an α-helix and β-strand is equal to 3 residues, but extends to 4 residues when located between two α-helices (α-3 10 -α) [28].…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the linearity of the reference peptide, we opted to design linear peptides. As a result we designed peptides with beta sheet forming amino acids namely cysteine, isoleucine, phenylalanine, threonine, tryptophan and tyrosine [ 39 , 40 ]. Proline and glycine were avoided to reduce folding of the peptide.…”
Section: Resultsmentioning
confidence: 99%